Temporal Stability and Practical Relevance of Velocity and Velocity-Loss Perception in Back Squat - Emanuele Dello Stritto; Antonio Gramazio; Ruggero Romagnoli; Maria Francesca Piacentini (Applied Sciences, 2025)
The aim of this study was to investigate the accuracy and stability of both Perception of Velocity (PV) and Perception of Velocity Loss (PVL) over four weeks, without any feedback regarding velocity during training sessions. Fifteen subjects performed six training sessions: four sessions familiarized the athletes with PV and PVL and the final two sessions assessed the accuracy and stability of PV and PVL, with one conducted 48 h after the familiarization and the other after 4 weeks. To assess PV and PVL, two loads (60% 1RM and 80% 1RM) and two velocity losses (20% VL and 40% VL) were employed. PV accuracy was measured by the DeltaScore, the difference between perceived velocity (Vp) and the velocity provided by the encoder (Vr): DetlaScore = Vp − Vr. PVL was measured by the Vscore, the difference between repetitions where the subject perceived the target %VL (Np) and repetitions that actually met it (Nr): Vscore = Np − Nr. The analysis performed revealed no differences in DeltaScore nor in Vscore between the two test sessions performed 4 weeks apart (p > 0.05). On the other hand, the effect of load on both DeltaScore and Vscore was significant in both sessions (p < 0.05). PVL and PV accuracy are stable throughout time. PVL may be used to prescribe and monitor velocity-based training. Conversely, when prescribing training sessions based on PV, it is essential to pair PV with a perception scale and incorporate an encoder when possible.